Administration of Shariah Criminal Justice under the Malaysian Constitutional Framework: Issues and Suggestions - Shuaib, Farid Sufian (LexisNexis, 2011)
Administration of Shariah criminal justice is only a small part of the judicial works in Shariah courts in Malaysia. The Shariah court system is a parallel court system to the civil court system with its own judicial officers, laws and procedures. Most of the courts' works involves marriage, divorce and distribution of Muslim estates. The administration of Shariah offences, although it only consists a small proportion of the courts' works, still manages to produce some constitutional issues. Competencies of the states to administer criminal law itself were questioned by some. These questions need to be considered by referring to the Federal Constitution as the main document in structuring the administration of justice. Similarly, any development or improvement to the administration must be anchored on the constitutional framework.